The association between epstein-barr virus and nasopharyngeal carcinoma - Mabaso, M.A (My University, 2022)
Background: Nasopharyngeal carcinoma (NPC) is a rare malignant neoplasm which has a wide age range but affects predominantly adult males. NPC is highly associated with Epstein-Barr virus. There are 3 histological subtypes described by the World Health Organisation (WHO), the commonest being the non-keratinizing subtype. Methods: In this retrospective study, confirmed cases of nasopharyngeal carcinoma were identified over a six and half year period in a South African population. The patient age, gender, HIV status and CD4 cell count were recorded where available. The site and type of biopsy, histological subtypes and EBER-ISH status of the tumour were also noted. Results: There were 120 cases of nasopharyngeal carcinoma during the study period. The age range was 10-75 years. The male to female ratio was 1.8:1. The most frequently biopsied site was the nasopharynx which constituted 74 (60.12%) cases. Of the 120 cases analysed, 110 cases (81.6 %) were classified as non-keratinizing nasopharyngeal carcinoma and there were two cases (1.68%) which were classified as keratinizing nasopharyngeal carcinoma. Eight cases (6.72%) could not be classified into any category. There were no cases of basaloid nasopharyngeal carcinoma in this cohort. EBER-ISH had been performed in 102 cases and 96 (94.1%) were positive. In these 96 cases, 87 (90.6%) cases were of the non-keratinizing subtype of NPC. HIV results were only available in 19 cases with 9 of these cases occurring in HIV positive patients. Of these 19 cases, CD4 cell counts were only available in 3 cases with a range of 300-900 cells/mm3. Conclusion: The study confirms that South African population shows nasopharyngeal carcinoma in a wide age range similar to other parts of the world. The most common histological subtype is non-keratinizing nasopharyngeal carcinoma. Nasopharyngeal carcinoma is strongly associated with Epstein-Barr virus in this population.
A dissertation submitted in fulfillment of the requirements for the degree of Master of Medicine in Anatomical Pathology to the Faculty of Health Sciences, School of Anatomical Sciences, University of the Witwatersrand, 2022